Chiral amine post-processed perovskite solar cell and preparation method thereof

The chiral amine post-treatment for perovskite solar cells addresses efficiency limitations by reducing defects and introducing an electron blocking layer, enhancing open circuit voltage and energy conversion efficiency.

CN119212524APending Publication Date: 2024-12-27GUILIN UNIV OF ELECTRONIC TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411441148.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Carbon-based printable mesoscopic perovskite solar cells (p-MPSCs) face limitations in energy conversion efficiency due to direct contact between perovskite and carbon, leading to charge recombination and voltage losses, with few achieving PCEs exceeding 20%.

Method used

A chiral amine post-treatment is applied to the perovskite crystal layer using a mixed solution of chiral amine molecules or chiral ammonium salts and alkyl amidine salts, forming a two-dimensional chiral perovskite that reduces voids and defects, and introduces an electron blocking layer at the perovskite/carbon interface.

Benefits of technology

The chiral amine post-treatment enhances the open circuit voltage and energy conversion efficiency of perovskite solar cells by inhibiting charge recombination and improving the perovskite/carbon electrode interface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005086364140000031
    Figure BDA0005086364140000031
  • Figure BDA0005086364140000032
    Figure BDA0005086364140000032
  • Figure BDA0005086364140000171
    Figure BDA0005086364140000171
Patent Text Reader

Abstract

The invention relates to a chiral amine post-processed perovskite solar cell and a preparation method thereof, and the method employs a chiral amine molecule or chiral ammonium salt and alkyl amidine salt mixed solution to carry out the post-processing of a perovskite optical active layer or a perovskite / carbon electrode interface, can passivate the defects of a perovskite film, inhibits the non-radiative recombination loss, and improves the photoelectric conversion efficiency. Therefore, the open-circuit voltage, the energy conversion efficiency and the long-term illumination stability of the perovskite solar cell are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of perovskite solar cells, and in particular to a chiral amine post-treated perovskite solar cell and a preparation method thereof. Background Art

[0002] Carbon-based printable mesoscopic perovskite solar cells (p-MPSCs) with a three-layer scaffold of pre-printed mesoporous titania (mp-TiO2) / mesoporous zirconia (mp-ZrO2) / porous carbon electrode structure have been demonstrated to have good stability, ultra-low cost and scalability. In p-MPSCs, perovskite is infiltrated into a pre-fabricated three-layer mesoscopic scaffold. The mp-TiO2 layer acts as an electron transport layer, the porous carbon acts as a back electrode and hole collection electrode, and the mp-ZrO2 layer provides insulation between the mp-TiO2 and carbon electrodes. Compared with other PSCs, p-MPSCs eliminate the need for an expensive hole transport layer and replace the expensive metal back electrode with a more economical carbon electrode. The carbon electrode and inorganic scaffold endow p-MPSCs with intrinsic stability by solving the stability issues associated with metal electrodes and organic functional layers. In addition, p-MPSCs can be fabricated using screen printing under ambient conditions, which facilitates scalable production and large-scale manufacturing. However, according to the "golden triangle" of perovskite solar cells, the energy conversion efficiency of p-MPSCs needs to be further improved. In p-MPSCs, the direct contact between perovskite and carbon hinders the formation of a hole-selective interface. The non-selective perovskite / carbon electrode interface makes the recombination process more likely to occur because both electrons and holes can be injected into the carbon electrode, which leads to a lower open circuit voltage of p-MPSCs. Due to the lack of electron blocking effect at the perovskite / carbon electrode interface, the energy level mismatch between perovskite and carbon electrode and the large number of defects at the grain boundaries still lead to considerable voltage losses and limit further improvements in device performance. Due to these limitations, only very few studies on p-MPSCs have reported PCEs exceeding 20%. Summary of the invention

[0003] In view of the deficiencies of the prior art, the present invention provides a chiral amine post-treated perovskite solar cell and a preparation method thereof, which can effectively reduce the void and body defect concentration of the perovskite film, and inhibit the generation of surface charge defects. At the same time, the perovskite / carbon electrode energy level arrangement is adjusted, and an electron blocking layer is formed at the perovskite / carbon electrode interface, which effectively inhibits the charge recombination at the perovskite / carbon electrode interface, thereby greatly improving the open circuit voltage, filling rate and energy conversion efficiency of the device.

[0004] The technical solution adopted by the present invention is:

[0005] The present invention provides a chiral amine post-treated perovskite solar cell and a preparation method thereof, wherein the preparation method comprises the following steps:

[0006] A substrate is provided, a functional layer is formed on the substrate, and a perovskite crystal layer is formed on the functional layer; a post-treatment solution is provided, the post-treatment solution is added to the perovskite crystal layer, and the solution is allowed to stand until the perovskite crystal layer is transformed into a perovskite layer; the post-treatment solution is a mixed solution of a chiral compound selected from a chiral amine molecule or a chiral ammonium salt and an alkyl amidine salt, preferably a C1-6 alkyl amidine salt.

[0007] Preferably, the chiral amine molecule or chiral ammonium salt has the following general structure:

[0008]

[0009] Wherein, R1 and R3 are each independently selected from halogen-substituted or unsubstituted aryl, C5-C6 cycloalkyl, C3-C6 azacycloalkyl, C1-C6 alkyl, R2 is selected from C1-C3 alkylene or does not exist; X is selected from halogen.

[0010] Preferably, R1 is selected from C1-C3 alkyl, and R3 is selected from halogen-substituted or unsubstituted phenyl, naphthyl, anthracenyl, pyrenyl, C5-C6 cycloalkyl, C4-C5 azacycloalkyl, C1-C6 alkyl.

[0011] Preferably, the chiral amine molecule is one or more non-racemic compounds selected from (S)-methylbenzylamine and (R)-methylbenzylamine, (S)-methylphenethylamine and (R)-methylphenethylamine, (S)-4-chlorophenylethylamine and (R)-4-chlorophenylethylamine, (S)-naphthylethylamine and (R)-naphthylethylamine, (S)-cyclohexylethylamine and (R)-cyclohexylethylamine, (S)-3-aminopiperidine and (R)-3-aminopiperidine, (S)-2-aminooctane and (R)-2-aminooctane, and the chiral ammonium salt is the hydrochloride, hydrobromide, hydroiodide, tetrafluoroborate or thiocyanate corresponding to the above chiral amine molecules. The chemical structure of the above preferred compounds is as follows (stereostructure is not marked):

[0012]

[0013] Preferably, the alkyl amidine salt is one or more of the hydrochloride, hydrobromide, hydroiodide, acetate, tetrafluoroborate or thiocyanate of a C1-C6 alkyl amidine.

[0014] Preferably, the chiral compound is a mixture of left-handed chiral amine molecules and right-handed chiral amine molecules, or a mixture of left-handed chiral ammonium salts and right-handed chiral ammonium salts, wherein the molar ratio of left-handed chiral amine molecules to right-handed chiral amine molecules (or left-handed chiral ammonium salts to right-handed chiral ammonium salts) is 0:10-10:0; the molar percentage of the alkyl amidine salt to the chiral amine molecules or chiral ammonium salts is 0.01%-200%; the concentration of the post-treatment solution is 0.01-1.00 g / ml;

[0015] Preferably, the solvent of the post-treatment solution is one or more of methanol, ethanol, propanol, butanol, amyl alcohol, isopropanol, isobutanol, isoamyl alcohol, toluene, chlorobenzene, chloroform, and acetonitrile;

[0016] Preferably, the step of standing comprises standing at a temperature of 0-150° C. for 0-24 hours;

[0017] Preferably, the perovskite crystal layer comprises ABX3, wherein A is selected from at least one of FA, MA and Cs, B is selected from at least one of Pb and Sn, and X is a halogen;

[0018] Preferably, the step of forming a functional layer on the substrate includes: forming a conductive layer on the substrate; forming a dense layer on the conductive layer; forming a mesoporous layer on the dense layer, and the mesoporous layer includes a mesoporous electron transport layer, a mesoporous spacer layer and a mesoporous counter electrode layer formed in sequence on the dense layer.

[0019] Preferably, the material of the mesoporous electron transport layer is selected from at least one of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3, the material of the mesoporous spacer layer is selected from at least one of ZrO2, SiO2, Al2O3, and BaTiO3, and the material of the mesoporous counter electrode layer is carbon.

[0020] Preferably, the chiral ammonium salt in the post-treatment solution reacts with PbI2 to form a two-dimensional chiral perovskite, or the chiral amine molecules in the post-treatment solution react with the alkyl amidine salt in advance to form larger cations, which then react with PbI2 to form a two-dimensional chiral perovskite, and the two-dimensional chiral perovskite and the chiral amine molecules or the chiral ammonium salt act synergistically at the perovskite / carbon electrode interface;

[0021] Further preferably, the preparation method of the perovskite solar cell specifically comprises the following steps: taking a mesoporous layer skeleton, filling it with a perovskite precursor solution to form a perovskite crystal layer, and then post-treating the perovskite crystal layer with a post-treatment solution, wherein the post-treatment solution is a mixed solution of chiral amine molecules or chiral ammonium salts and alkyl amidine salts, the chiral amine molecules are a mixture of left-handed chiral amine molecules and right-handed chiral amine molecules, and the molar ratio of the left-handed chiral amine molecules to the right-handed chiral amine molecules (or the left-handed chiral ammonium salts to the right-handed chiral ammonium salts) is 0:10-10:0; the alkyl amidine salt accounts for 1:1% of the chiral amine The molar percentage of the molecules or chiral ammonium salts is 0.01%-200%, and is allowed to stand at a temperature of 0-150°C for 0 to 24 hours; the concentration of the post-treatment solution is 0.01-1.00g / ml; the chiral ammonium salt reacts with PbI2 to form a two-dimensional chiral perovskite by post-treating the porous membrane skeleton, or the chiral amine molecules in the post-treatment solution react with the alkyl amidine salt in advance to form larger cations, which then react with PbI2 to form a two-dimensional chiral perovskite, and the two-dimensional chiral perovskite acts synergistically with the chiral amine molecules or chiral ammonium salts at the perovskite / carbon electrode interface.

[0022] The present invention further provides a perovskite solar cell, which is prepared by the above method.

[0023] The beneficial effects of the present invention are:

[0024] The present invention uses chiral amine molecules or a mixed solution of chiral ammonium salt and alkyl amidine salt dissolved in an organic solvent as a post-treatment solution to post-treat the perovskite crystal layer. The chiral ammonium salt in the post-treatment solution reacts with PbI2 to form a two-dimensional chiral perovskite, or the chiral amine molecules in the post-treatment solution react with the alkyl amidine salt in advance to form a larger cation, which then reacts with PbI2 to form a two-dimensional chiral perovskite. The two-dimensional chiral perovskite and the chiral amine molecules or chiral ammonium salt act synergistically on the perovskite / carbon electrode interface. By combining the organic-inorganic hybrid perovskite component with chirality, the introduction of chiral amine molecules or chiral amine salts can make the perovskite crystallize in a chiral space group and present chiral characteristics. The chiral two-dimensional perovskite breaks the spatial inversion symmetry of the perovskite crystal and establishes a chiral-ferroelectric heterojunction polarity system. The remnant polarization field effect of the ferroelectric material can be used to obtain a high-voltage ferroelectric photovoltaic device. At the same time, since a wide-bandgap two-dimensional perovskite interface layer material is constructed between the perovskite and the mesoporous electrode layer, the mismatch between the perovskite and the mesoporous electrode layer of the carbon electrode can be reduced, the open circuit voltage of the device can be increased, and thus the device efficiency can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1It is a JV curve graph of Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5, and Example 1, Example 2, and Example 3 of the present invention tested in air under unpackaged conditions. DETAILED DESCRIPTION

[0026] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work all fall within the scope of protection of the present invention.

[0027] Comparative Example 1:

[0028] This comparative example provides a perovskite solar cell that has not been post-treated with a chiral amine molecule or a mixed solution of a chiral ammonium salt and an alkyl amidine salt, comprising the following steps:

[0029] (1) Preparation of mesoscopic perovskite solar cells: On a FTO glass substrate, a 40 nm thick dense titanium dioxide film was prepared by spray pyrolysis, a 600 nm thick mesoporous titanium dioxide layer was prepared by printing, a 2 μm thick mesoporous zirconium oxide layer was prepared by printing, and a 20 μm thick carbon electrode was prepared by printing carbon slurry. After sintering at 400 °C and cooling to room temperature, 5 μL of Cs was drop-coated on the top of the mesoporous carbon electrode. 0.05 MA 0.15 FA 0.8 PbI3·MACl 0.2 The perovskite precursor solution infiltrates and fills the mesoporous zirconia and mesoporous titanium dioxide from top to bottom from the mesoporous carbon electrode in sequence, and a perovskite solar cell is prepared after annealing at 60°C for 20 hours.

[0030] The perovskite solar cell obtained in step (1) without post-treatment with the chiral amine molecule or the mixed solution of chiral ammonium salt and alkyl amidine salt was tested by JV curve. The short-circuit current density of the solar cell was 23.87 mA cm -2 , the open circuit voltage is 0.97V, the fill factor is 75.57%, and the energy conversion efficiency is 17.46%.

[0031] Comparative Example 2:

[0032] This comparative example provides a perovskite solar cell in which a chiral amine molecule or a mixed solution of a chiral ammonium salt and an alkyl amidine salt is added to a perovskite precursor solution, comprising the following steps:

[0033] (1) Preparation of mesoscopic perovskite solar cells: On a FTO glass substrate, a 40 nm thick dense titanium dioxide film was prepared by spray pyrolysis, a 600 nm thick mesoporous titanium dioxide layer was prepared by printing, a 2 μm thick mesoporous zirconium oxide layer was prepared by printing, and a 20 μm thick carbon electrode was prepared by printing carbon slurry. After sintering at 400°C and cooling to room temperature, 5 μL of Cs containing 5% chiral methylbenzylamine (wherein (S)-methylbenzylamine: (R)-methylbenzylamine = 5:5, and the molar percentage of formamidine hydroiodide in the (S)-methylbenzylamine and (R)-methylbenzylamine is 10%) was drop-coated on the mesoporous carbon electrode. 0.05 MA 0.15 FA 0.8 PbI3·MACl 0.2 (1 mol / L) perovskite precursor solution was used to infiltrate and fill the mesoporous zirconia and mesoporous titania from top to bottom from the mesoporous carbon electrode. After annealing at 60°C for 20h, a mesoscopic perovskite solar cell was prepared.

[0034] The perovskite solar cell obtained in step (1) containing chiral methylbenzylamine in the perovskite precursor solution (wherein the molar ratio of (S)-methylbenzylamine to (R)-methylbenzylamine is 5:5) was subjected to a JV curve test. The short-circuit current density of the solar cell was 23.35 mA cm -2 , the open circuit voltage is 0.96V, the fill factor is 70.51%, and the energy conversion efficiency is 15.74%.

[0035] Comparative Example 3:

[0036] This comparative example provides a perovskite solar cell and a preparation method thereof which is post-treated with a mixed solution of 1.01 g / ml chiral amine molecules or chiral ammonium salts and formamidine hydroiodide, wherein the molar percentage of formamidine hydroiodide in the chiral amine molecules or chiral ammonium salts is 0.01% to 200%. The method comprises the following steps:

[0037] (1) Preparation of mesoscopic perovskite solar cells: On a FTO glass substrate, a 40 nm thick dense titanium dioxide film was prepared by spray pyrolysis, a 600 nm thick mesoporous titanium dioxide layer was prepared by printing, a 2 μm thick mesoporous zirconium oxide layer was prepared by printing, and a 20 μm thick carbon electrode was prepared by printing carbon slurry. After sintering at 400 °C and cooling to room temperature, 5 μL of Cs was drop-coated on the top of the mesoporous carbon electrode. 0.05 MA 0.15 FA 0.8 PbI3·MACl 0.2 The perovskite precursor solution infiltrates and fills the mesoporous zirconia and mesoporous titanium dioxide from top to bottom from the mesoporous carbon electrode in sequence, and a perovskite solar cell is prepared after annealing at 60°C for 20 hours.

[0038] (2) Post-treatment of a mixed solution of chiral amine molecules or chiral ammonium halides and formamidine hydroiodide: A 1.01 g / ml isopropanol solution of chiral methylbenzylamine and formamidine hydroiodide (wherein the molar ratio of (S)-methylbenzylamine to (R)-methylbenzylamine is 6:4, and the molar percentage of formamidine hydroiodide to the (S)-methylbenzylamine and (R)-methylbenzylamine is 40%) is coated on a carbon electrode, and then annealed at 25°C for 75 min to form a perovskite solar cell based on chiral amine treatment.

[0039] The perovskite solar cell obtained by post-treatment with an isopropanol solution of chiral methylbenzylamine and formamidine hydroiodide in this comparative example was subjected to a JV curve test, and its short-circuit current density was 19.65 mA cm -2 , the open circuit voltage is 0.88 V, the fill factor is 80.79%, and the energy conversion efficiency is 13.89%, indicating that post-treatment with a chiral amine molecule or a mixed solution of chiral halogen ammonium salt and alkyl amidine salt with a concentration higher than 1 g / ml cannot improve the energy conversion efficiency of perovskite solar cells.

[0040] Comparative Example 4:

[0041] This comparative example provides a perovskite solar cell and a preparation method thereof that is post-treated with a mixed solution of 0.50 g / ml chiral amine molecules or chiral ammonium salts and formamidine hydroiodide, wherein the molar percentage of formamidine hydroiodide in the chiral amine molecules or chiral ammonium salts is greater than 200%. The steps include:

[0042] (1) Preparation of mesoscopic perovskite solar cells: On a FTO glass substrate, a 40 nm thick dense titanium dioxide film was prepared by spray pyrolysis, a 600 nm thick mesoporous titanium dioxide layer was prepared by printing, a 2 μm thick mesoporous zirconium oxide layer was prepared by printing, and a 20 μm thick carbon electrode was prepared by printing carbon slurry. After sintering at 400 °C and cooling to room temperature, 5 μL of Cs was drop-coated on the top of the mesoporous carbon electrode. 0.05 MA 0.15 FA 0.8 PbI3·MACl 0.2 The perovskite precursor solution infiltrates and fills the mesoporous zirconia and mesoporous titanium dioxide from top to bottom from the mesoporous carbon electrode in sequence, and a perovskite solar cell is prepared after annealing at 60°C for 20 hours.

[0043] (2) Post-treatment with a mixed solution of chiral amine molecules or chiral ammonium halides and formamidine hydroiodide: A 0.50 g / ml isopropanol solution of chiral methylbenzylamine and iodoformamidine (wherein the molar ratio of (S)-methylbenzylamine to (R)-methylbenzylamine is 6:4, and the molar percentage of formamidine hydroiodide to the (S)-methylbenzylamine and (R)-methylbenzylamine is 210%) is coated on a carbon electrode, and then annealed at 25°C for 75 min to form a perovskite solar cell based on chiral amine treatment.

[0044] The perovskite solar cell obtained by post-treatment with an isopropanol solution of chiral methylbenzylamine and formamidine hydroiodide in this comparative example was subjected to a JV curve test, and its short-circuit current density was 23.88 mA cm -2 , the open circuit voltage is 0.95 V, the fill factor is 72.45%, and the energy conversion efficiency is 16.47%, indicating that post-treatment of a mixed solution of chiral amine molecules or chiral halogen ammonium salts and alkyl amidine salts in which the molar percentage of formamidine hydroiodide in the chiral amine molecules or chiral ammonium salts is greater than 210% cannot improve the energy conversion efficiency of perovskite solar cells.

[0045] Comparative Example 5:

[0046] This comparative example provides a perovskite solar cell without 0.15 g / ml of alkyl amidine salt and post-treatment of chiral amine molecules or chiral ammonium salts and a preparation method thereof, wherein the molar percentage of the alkyl amidine salt in the chiral amine molecules or chiral ammonium salts is 0%. The steps include:

[0047] (1) Preparation of mesoscopic perovskite solar cells: On a FTO glass substrate, a 40 nm thick dense titanium dioxide film was prepared by spray pyrolysis, a 600 nm thick mesoporous titanium dioxide layer was prepared by printing, a 2 μm thick mesoporous zirconium oxide layer was prepared by printing, and a 20 μm thick carbon electrode was prepared by printing carbon slurry. After sintering at 400 °C and cooling to room temperature, 5 μL of Cs was drop-coated on the top of the mesoporous carbon electrode. 0.05 MA 0.15 FA 0.8 PbI3·MACl 0.2 The perovskite precursor solution infiltrates and fills the mesoporous zirconia and mesoporous titanium dioxide from top to bottom from the mesoporous carbon electrode in sequence, and a perovskite solar cell is prepared after annealing at 60°C for 20 hours.

[0048] (2) Post-treatment of chiral amine molecules or chiral halogen ammonium salts: A 0.15 g / ml isopropanol solution of chiral methylbenzylamine and alkyl amidine salt (wherein the molar ratio of (S)-methylbenzylamine to (R)-methylbenzylamine is 6:4, and the molar percentage of alkyl amidine salt to the (S)-methylbenzylamine and (R)-methylbenzylamine is 0%) is coated on a carbon electrode, and then annealed at 25°C for 75 min to form a perovskite solar cell based on chiral amine treatment.

[0049] The perovskite solar cell obtained by post-treatment with isopropanol solution of chiral methylbenzylamine in this comparative example was subjected to JV curve test, and its short-circuit current density was 25.93 mA cm -2, the open circuit voltage is 1.02V, the fill factor is 72.87%, and the energy conversion efficiency is 19.24%, indicating that chiral amine molecules or chiral halogen ammonium salts without alkyl amidine salts can improve the energy conversion efficiency of perovskite solar cells, but compared with chiral amine molecules or chiral halogen ammonium salts containing alkyl amidine salts, perovskite solar cells have lower open circuit voltage and fill factor.

[0050] Embodiment 1:

[0051] This embodiment provides a mesoscopic perovskite solar cell post-treated with a mixed solution of 0.03 g / ml chiral amine molecules or chiral ammonium salts and formamidine hydroiodide and a preparation method thereof, comprising the following steps:

[0052] (1) Preparation of mesoscopic perovskite solar cells: On a FTO glass substrate, a 40 nm thick dense titanium dioxide film was prepared by spray pyrolysis, a 600 nm thick mesoporous titanium dioxide layer was prepared by printing, a 2 μm thick mesoporous zirconium oxide layer was prepared by printing, and a 20 μm thick carbon electrode was prepared by printing carbon slurry. After sintering at 400 °C and cooling to room temperature, 5 μL of Cs was drop-coated on the top of the mesoporous carbon electrode. 0.05 MA 0.15 FA 0.8 PbI3·MACl 0.2 The perovskite precursor solution infiltrates and fills the mesoporous zirconia and mesoporous titanium dioxide from top to bottom from the mesoporous carbon electrode in sequence, and a perovskite solar cell is prepared after annealing at 60°C for 20 hours.

[0053] (2) Post-treatment of a mixed solution of chiral amine molecules or chiral ammonium halides and formamidine hydroiodide: A 0.03 g / ml isopropanol solution of chiral methylbenzylamine and formamidine hydroiodide (wherein the molar ratio of (S)-methylbenzylamine to (R)-methylbenzylamine is 6:4, and the molar percentage of formamidine hydroiodide to the (S)-methylbenzylamine and (R)-methylbenzylamine is 40%) is coated on a carbon electrode, and then annealed at 75°C for 25 min to form a perovskite solar cell based on chiral amine treatment.

[0054] In this embodiment, the perovskite solar cell obtained by post-treatment with an isopropanol solution of chiral methylbenzylamine and formamidine hydroiodide was subjected to a JV curve test, and its short-circuit current density was 25.92 mA cm -2 , the open circuit voltage is 1.03V, the fill factor is 79.05%, and the energy conversion efficiency is 21.15%, indicating that post-treatment with 0.03mg / ml chiral amine molecules or a mixed solution of chiral halogen ammonium salts and formamidine hydroiodide (wherein the molar ratio of (S)-methylbenzylamine to (R)-methylbenzylamine is 6:4, and the molar percentage of formamidine hydroiodide to the (S)-methylbenzylamine and (R)-methylbenzylamine is 40%) can improve the energy conversion efficiency of perovskite solar cells.

[0055] Embodiment 2:

[0056] This embodiment provides a perovskite solar cell post-treated with a mixed solution of 0.6 g / ml chiral amine molecules or chiral ammonium salts and formamidine hydroiodide and a preparation method thereof, comprising the following steps:

[0057] (1) Preparation of perovskite solar cells: On a FTO glass substrate, a 40 nm thick dense titanium dioxide film was prepared by spray pyrolysis, a 600 nm thick mesoporous titanium dioxide layer was prepared by printing, a 2 μm thick mesoporous zirconium oxide layer was prepared by printing, and a 20 μm thick carbon electrode was prepared by printing carbon slurry. After sintering at 400 °C and cooling to room temperature, 5 μL of Cs was drop-coated on the top of the mesoporous carbon electrode. 0.05 MA 0.15 FA 0.8 PbI3·MACl 0.2 The perovskite precursor solution infiltrates and fills the mesoporous zirconia and mesoporous titanium dioxide from top to bottom from the mesoporous carbon electrode in sequence, and a perovskite solar cell is prepared after annealing at 60°C for 20 hours.

[0058] (2) Post-treatment of isopropanol solution of chiral 1-(1-naphthyl)ethylamine and formamidine hydroiodide: A 0.6 g / ml isopropanol solution of chiral 1-(1-naphthyl)ethylamine and formamidine hydroiodide (wherein the molar ratio of (S)-1-(1-naphthyl)ethylamine to (R)-1-(1-naphthyl)ethylamine is 5:5, and the molar percentage of formamidine hydroiodide to the (S)-1-(1-naphthyl)ethylamine and (R)-1-(1-naphthyl)ethylamine is 100%) is coated on a carbon electrode, and then annealed at 25°C for 15 min to form a perovskite solar cell based on a chiral perovskite heterojunction.

[0059] In this embodiment, the perovskite solar cell obtained by post-treatment with isopropanol solution of chiral 1-(1-naphthyl)ethylamine and formamidine hydroiodide was subjected to JV curve test, and its short-circuit current density was 26.03 mA cm -2 , the open circuit voltage is 1.04V, the fill factor is 78.96%, and the energy conversion efficiency is 21.40%, indicating that post-treatment with 0.6g / ml chiral amine molecules or chiral halogen ammonium salts and formamidine hydroiodide mixed solution (wherein the molar ratio of (S)-1-(1-naphthyl)ethylamine to (R)-1-(1-naphthyl)ethylamine is 5:5, and the molar percentage of formamidine hydroiodide to the (S)-1-(1-naphthyl)ethylamine and (R)-1-(1-naphthyl)ethylamine is 100%) can improve the energy conversion efficiency of perovskite solar cells.

[0060] Embodiment 3:

[0061] This embodiment provides a perovskite solar cell post-treated with a mixed solution of 0.9 g / ml chiral amine molecules or chiral ammonium salts and formamidine hydroiodide and a preparation method thereof, comprising the following steps:

[0062] (1) Preparation of perovskite solar cells: On a FTO glass substrate, a 40 nm thick dense titanium dioxide film was prepared by spray pyrolysis, a 600 nm thick mesoporous titanium dioxide layer was prepared by printing, a 2 μm thick mesoporous zirconium oxide layer was prepared by printing, and a 20 μm thick carbon electrode was prepared by printing carbon slurry. After sintering at 400 °C and cooling to room temperature, 5 μL of Cs was drop-coated on the mesoporous carbon electrode. 0.05 MA 0.15 FA 0.8 PbI3·MACl 0.2 The perovskite precursor solution infiltrates and fills the mesoporous zirconia and mesoporous titanium dioxide from top to bottom from the mesoporous carbon electrode in sequence, and a perovskite solar cell is prepared after annealing at 60°C for 20 hours.

[0063] (2) Post-treatment with a mixed solution of chiral amine molecules or chiral ammonium halogen salts and formamidine hydroiodide: A 0.9 g / ml isopropanol solution of chiral 2-aminooctane and formamidine hydroiodide (wherein the molar ratio of (S)-2-aminooctane to (R)-2-aminooctane is 2:8, and the molar percentage of formamidine hydroiodide to the (S)-2-aminooctane and (R)-2-aminooctane is 120%) is coated on a carbon electrode, and then annealed at 75°C for 25 min to form a perovskite solar cell based on chiral amine treatment.

[0064] In this embodiment, the solar cell obtained by post-treatment with the isopropanol solution of chiral 2-aminooctane and formamidine hydroiodide was subjected to JV curve test, and its short-circuit current density was 25.94 mA cm -2 , the open circuit voltage is 1.05V, the fill factor is 78.18%, and the energy conversion efficiency is 21.23%. This indicates that the post-treatment of 0.9g / ml chiral 2-aminooctane and formamidine hydroiodide isopropanol solution (wherein the molar ratio of (S)-2-aminooctane to (R)-2-aminooctane is 2:8, and the molar percentage of formamidine hydroiodide to the (S)-2-aminooctane and (R)-2-aminooctane is 120%) can improve the energy conversion efficiency of perovskite solar cells.

[0065] Embodiment 4:

[0066] This embodiment provides a perovskite solar cell post-treated with a mixed solution of 0.8 g / ml chiral amine molecules or chiral ammonium salts and formamidine acetate and a preparation method thereof, comprising the following steps:

[0067] (1) Preparation of perovskite solar cells: On a FTO glass substrate, a 40 nm thick dense titanium dioxide film was prepared by spray pyrolysis, a 600 nm thick mesoporous titanium dioxide layer was prepared by printing, a 2 μm thick mesoporous zirconium oxide layer was prepared by printing, and a 20 μm thick carbon electrode was prepared by printing carbon slurry. After sintering at 400 °C and cooling to room temperature, 5 μL of Cs was drop-coated on the mesoporous carbon electrode. 0.05 MA 0.15 FA 0.8 PbI3·MACl 0.2 The perovskite precursor solution infiltrates and fills the mesoporous zirconia and mesoporous titanium dioxide from top to bottom from the mesoporous carbon electrode in sequence, and a perovskite solar cell is prepared after annealing at 60°C for 20 hours.

[0068] (2) Post-treatment with a mixed solution of chiral amine molecules or chiral ammonium halides and formamidine acetate: A 0.8 g / ml isopropanol solution of chiral 2-aminooctane and formamidine acetate (wherein the molar ratio of (S)-2-aminooctane to (R)-2-aminooctane is 6:4, and the molar percentage of formamidine acetate to the (S)-2-aminooctane and (R)-2-aminooctane is 100%) is coated on a carbon electrode, and then annealed at 75°C for 25 min to form a perovskite solar cell based on chiral amine treatment.

[0069] In this embodiment, the solar cell obtained by post-treatment with the isopropanol solution of chiral 2-aminooctane and formamidine acetate was subjected to JV curve test, and its short-circuit current density was 25.66 mA cm -2 , the open circuit voltage is 1.05V, the fill factor is 78.93%, and the energy conversion efficiency is 21.23%. This indicates that the post-treatment of 0.8g / ml chiral 2-aminooctane and formamidine acetate isopropanol solution (wherein the molar ratio of (S)-2-aminooctane to (R)-2-aminooctane is 6:4, and the molar percentage of formamidine acetate to the (S)-2-aminooctane and (R)-2-aminooctane is 100%) can improve the energy conversion efficiency of perovskite solar cells.

[0070] Embodiment 5:

[0071] This embodiment provides a perovskite solar cell post-treated with a mixed solution of 0.06 g / ml chiral amine molecules or chiral ammonium salts and pentamidine hydroiodide and a preparation method thereof, comprising the following steps:

[0072] (1) Preparation of perovskite solar cells: On a FTO glass substrate, a 40 nm thick dense titanium dioxide film was prepared by spray pyrolysis, a 600 nm thick mesoporous titanium dioxide layer was prepared by printing, a 2 μm thick mesoporous zirconium oxide layer was prepared by printing, and a 20 μm thick carbon electrode was prepared by printing carbon slurry. After sintering at 400 °C and cooling to room temperature, 5 μL of Cs was drop-coated on the top of the mesoporous carbon electrode.0.05 MA 0.15 FA 0.8 PbI3·MACl 0.2 The perovskite precursor solution infiltrates and fills the mesoporous zirconia and mesoporous titanium dioxide from top to bottom from the mesoporous carbon electrode in sequence, and a perovskite solar cell is prepared after annealing at 60°C for 20 hours.

[0073] (2) Post-treatment of isopropanol solution of chiral 1-(1-naphthyl)ethylamine and pentamidine hydroiodide: A 0.6 g / ml isopropanol solution of chiral 1-(1-naphthyl)ethylamine and pentamidine hydroiodide (wherein the molar ratio of (S)-1-(1-naphthyl)ethylamine to (R)-1-(1-naphthyl)ethylamine is 5:5, and the molar percentage of pentamidine hydroiodide to the (S)-1-(1-naphthyl)ethylamine and (R)-1-(1-naphthyl)ethylamine is 50%) is coated on a carbon electrode, and then annealed at 25°C for 15 min to form a perovskite solar cell based on a chiral perovskite heterojunction.

[0074] In this embodiment, the perovskite solar cell obtained by post-treatment with isopropanol solution of chiral 1-(1-naphthyl)ethylamine and pentamidine hydroiodide was subjected to JV curve test, and its short-circuit current density was 26.03 mA cm -2 , the open circuit voltage is 1.04V, the fill factor is 78.96%, and the energy conversion efficiency is 21.40%, indicating that post-treatment with 0.06g / ml chiral amine molecules or chiral halogen ammonium salts and pentamidine hydroiodide mixed solution (wherein the molar ratio of (S)-1-(1-naphthyl)ethylamine to (R)-1-(1-naphthyl)ethylamine is 5:5, and the molar percentage of pentamidine hydroiodide to the (S)-1-(1-naphthyl)ethylamine and (R)-1-(1-naphthyl)ethylamine is 50%) can improve the energy conversion efficiency of perovskite solar cells.

[0075] The short-circuit current density, open-circuit voltage, fill factor, and energy conversion efficiency values ​​of Comparative Examples 1-5 and Examples 1-5 are shown in Table 1

[0076] Table 1

[0077]

Claims

1. A method for preparing a perovskite solar cell, characterized in that: include: Providing a substrate, forming a functional layer on the substrate, and forming a perovskite crystal layer on the functional layer; providing a post-treatment solution, adding the post-treatment solution onto the perovskite crystal layer, and allowing the solution to stand until the perovskite crystal layer is transformed into a perovskite layer; The post-treatment solution is a mixed solution of a chiral compound selected from a chiral amine molecule or a chiral ammonium salt and an alkyl amidine salt.

2. The preparation method according to claim 1, characterized in that: The chiral compound is a mixture of left-handed chiral amine molecules and right-handed chiral amine molecules, or a mixture of left-handed chiral ammonium salts and right-handed chiral ammonium salts, wherein the molar ratio of left-handed chiral amine molecules to right-handed chiral amine molecules or left-handed chiral ammonium salts to right-handed chiral ammonium salts is 0:10 to 10:0; the molar percentage of the alkyl amidine salt to the chiral amine molecules or the chiral ammonium salts is 0.01% to 200%; and the concentration of the post-treatment solution is 0.01-1.00 g / ml.

3. The preparation method according to claim 1, characterized in that: The perovskite crystal layer includes an ABX3 perovskite structure, wherein A is selected from at least one of FA, MA and Cs, B is selected from at least one of Pb and Sn, and X is a halogen.

4. The preparation method according to claim 1, characterized in that: The alkyl amidine salt is a C1-C6 alkyl amidine salt.

5. The preparation method according to claim 1, characterized in that: The chiral amine molecule or chiral ammonium salt has the following general structure: Wherein, R1 and R3 are independently selected from halogen-substituted or unsubstituted aryl, C5-C6 cycloalkyl, C3-C6 azacycloalkyl, C1-C6 alkyl, R2 is selected from C1-C3 alkylene or does not exist; X is selected from halogen; preferably, R1 is selected from C1-C3 alkyl, R3 is selected from halogen-substituted or unsubstituted phenyl, naphthyl, anthracenyl, pyrenyl, C5-C6 cycloalkyl, C4-C5 azacycloalkyl, C1-C6 alkyl; the most preferred chiral amine molecules are: (S)-methylbenzylamine and (R)-methylbenzylamine, (S)-methylphenethylamine and (R)-methylphenethylamine, (S)-4-chlorophenyl One or more non-racemic compounds selected from ethylamine and (R)-4-chlorophenylethylamine, (S)-naphthylethylamine and (R)-naphthylethylamine, (S)-cyclohexylethylamine and (R)-cyclohexylethylamine, (S)-3-aminopiperidine and (R)-3-aminopiperidine, (S)-2-aminooctane and (R)-2-aminooctane, the halogen ammonium salt being one or more of the hydrochloride, hydrobromide, hydroiodide, tetrafluoroborate or thiocyanate corresponding to the above chiral amine molecules, and the alkyl amidine salt being one or more of the hydrochloride, hydrobromide, hydroiodide, acetate, tetrafluoroborate or thiocyanate of C1-C6 alkyl amidine.

6. The preparation method according to claim 1, characterized in that: The solvent of the post-treatment solution is one or more of methanol, ethanol, propanol, butanol, amyl alcohol, isopropanol, isobutanol, isopentanol, toluene, chlorobenzene, and chloroform.

7. The preparation method according to claim 1, characterized in that: The step of forming a functional layer on the substrate includes: forming a conductive layer on the substrate; forming a dense layer on the conductive layer; forming a mesoporous layer on the dense layer, wherein the mesoporous layer includes a mesoporous electron transport layer, a mesoporous spacer layer and a mesoporous counter electrode layer which are sequentially formed on the dense layer.

8. The preparation method according to claim 1, characterized in that: The step of forming the perovskite crystal layer includes: providing a perovskite precursor solution, wherein the perovskite precursor solution is obtained by adding at least one of MAX, FAX, CsX, and at least one of PbX2 and SnX2 to a solvent, where X is a halogen; adding the perovskite precursor solution to the functional layer to form a perovskite wet film layer; and curing the perovskite wet film layer to form the perovskite crystal layer.

9. The preparation method according to claim 7, characterized in that: The material of the mesoporous electron transport layer is selected from at least one of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3; the material of the mesoporous spacer layer is selected from at least one of ZrO2, SiO2, Al2O3, and BaTiO3; and the material of the mesoporous counter electrode layer is carbon.

10. A perovskite solar cell, characterized in that: The method is obtained by the preparation method according to any one of claims 1 to 9.